Painting Indiana III : heritage of place - Perry, Rachel Berenson (Indiana University Press, 2013)
The work of T.C. Steele, William Forsyth, J. Ottis Adams, Otto Stark, and Richard Gruelle, known collectively as the Hoosier Group, established plein air ("in the open air") painting as a major art form in Indiana. The vitality of this style is represented in this book, which includes 100 juried works by Indiana plein air artists, along with paintings by the Hoosier Group, all featuring notable Indiana landmarks. This book will delight both Hoosiers and art lovers around the world.